2013
DOI: 10.14219/jada.archive.2013.0016
|View full text |Cite
|
Sign up to set email alerts
|

The dentist's role in promoting community water fluoridation

Abstract: Background and Overview Community water fluoridation is an important public health intervention that reduces oral health disparities and increases the health of the population. Promotion of its safety and effectiveness is critical to maintaining its widespread acceptance and ensuring its continued use. Dentists are a potentially important source of knowledge regarding the oral health benefits and safety of water fluoridation. However, few dentists regularly discuss fluorides, and water fluoridation in particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…The findings of this study regarding the role of dental education in preventive dentistry are in line with other studies (18, 19) which have concluded that current undergraduate dental curricula do not adequately prepare dentists for prevention-oriented treatment, and the public health role and continuing dental education may be insufficient to change clinical practice. Participants’ opinions on practice-related barriers are consistent with others expressed by dentists in earlier research in Iran (6) and Mongolia (12) and may support the idea that that informed and motivated dentists are lacking the support from policy makers to enhance preventive dental programmes (20).…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this study regarding the role of dental education in preventive dentistry are in line with other studies (18, 19) which have concluded that current undergraduate dental curricula do not adequately prepare dentists for prevention-oriented treatment, and the public health role and continuing dental education may be insufficient to change clinical practice. Participants’ opinions on practice-related barriers are consistent with others expressed by dentists in earlier research in Iran (6) and Mongolia (12) and may support the idea that that informed and motivated dentists are lacking the support from policy makers to enhance preventive dental programmes (20).…”
Section: Discussionsupporting
confidence: 90%
“…57–59 There are mixed results in regards to the preventive benefit of fluoride rinses among older adults. 60,61 Numerous studies indicate that older adults benefit from water fluoridation 22,62,63 , which reinforces the importance of dental health professionals being prepared to speak to patients about the oral health benefits associated with community water fluoridation 64 .…”
Section: Discussionmentioning
confidence: 94%
“…However water fluoridation since its initiation has attracted hostile publicity, those who do not put a value on water fluoridation caution that it is; costly and not effective, that it impacts negatively on general health; causes objectionable dental fluorosis and that it is a violation of medical ethics and the rights of the individual (39). Thus the very core of its capacity to promote prevention to the whole population is challenged.…”
Section: The Risk Of Water Fluoridationmentioning
confidence: 99%